“THE CART BEFORE THE HORSE: THE PRIORITY OF SCIENCE AND POLITICS” - Phillips, Clarence Mark (European Scientific Journal, ESJ, 2015)
In 1959, C.P. Snow claimed that contemporary society had become divided into two distinct cultures – the arts and sciences – and showed how this academic divide was connected to a real world economic split between the haves and have-nots. Today, the division is more often between science and politics, creating a rift between empirical fact and public policy. When facing global challenges such as resource depletion, dwindling biodiversity, escalating populations, and increased CO2 levels, should popular opinion be allowed to trump empirical data? Or should policy makers be forced to rule along scientific guidelines? And is there a danger of losing civil liberties to the dictates of scientifically-run government bodies? Throughout human history we have struggled with the distinction between “is” and “ought”: whether facts should (or even can) determine values. In communities of open inquiry, we must also consider the relation between education and social order: whether to require that citizens be educated in the sciences in order to vote on matters of public concern, or to allow the will of an uninformed populace to take precedence over matters of sheer fact. Genuinely democratic society requires an educated public, but raises questions of intellectual freedom: what should we teach? The global society of the 21st Century will face this issue in a variety of ways. If our differences matter less than our commonality – and even threaten it – nothing may matter more than that our public policies reflect our collective scientific understanding. So, a world-wide community must entail increased focus on education.